A conditionally integrable bi-confluent Heun potential involving inverse square root and centrifugal barrier terms; Zeitschrift fur Naturforschung - Section A Journal of Physical Sciences; Vol. 73, iss. 5 - energy spectrum T. A. Tigran Arturovich (2018, 2018)
Title screen